ProgNet: A Social Network for University Community - Omar, Bourahla; Imane, Bourahla; Supervisor: Noureddine, Amraoui (Mohamed Boudiaf University of M'sila, 2025)
This report presents ProgNet, a mobile-first academic social networking platform developed to meet the specific communication and collaboration needs of Algerian university communities. ProgNet addresses the limitations of relying on general-purpose platforms such as Facebook for academic interaction by offering a secure, role-based, and university-controlled environment. The system enables students, teachers, to create and manage profiles, share educational content, publish department news, organize events, enroll in classes, and engage in direct communication. Built using modern web and mobile technologies, ProgNet integrates third-party services like Supabase for media management and Firebase for real-time notifications. This technical report documents the full development lifecycle of ProgNet, starting from functional analysis and security requirements definition, through architectural design using C4 and UML models, until system implementation and deployment. The system relies on a flexible backend architecture and an interactive mobile app built with Flutter, ensuring a seamless and efficient user experience.
Keywords: Social Networking; Academic Communication; Digital Platforms; Information Systems; Flutter; Node.js.